No-meat eaters are less likely to be overweight or obese, but take dietary supplements more often: results from the Swiss National Nutrition survey menuCH. Issue 13 (7th September 2021) - Steinbach, Lydia; Rohrmann, Sabine; Kaelin, Ivo; Krieger, Jean-Philippe; Pestoni, Giulia; Herter-Aeberli, Isabel; Faeh, David; Sych, Janice
Abstract: Objective: To describe and analyse the sociodemographic, anthropometric, behavioural and dietary characteristics of different types of Swiss (no-)meat eaters. Design: No-, low-, medium- and high-meat eaters were compared with respect to energy and total protein intake and sociodemographic, anthropometric and behavioural characteristics. Setting: National Nutrition Survey menuCH, the first representative survey in Switzerland. Participants: 2057 participants, aged 18–75 years old, who completed two 24-h dietary recalls (24-HDR) and a questionnaire on dietary habits, sociodemographic and lifestyle factors. Body weight and height were measured by trained interviewers. No-meat eaters were participants who reported meat avoidance in the questionnaire and did not report any meat consumption in the 24-HDR. Remaining study participants were assigned to the group of low-, medium- or high-meat eaters based on energy contributions of total meat intake to total energy intake (meat:energy ratio). Fifteen percentage of the participants were assigned to the low- and high-meat eating groups, and the remaining to the medium-meat eating group. Results: Overall, 4·4 % of the study participants did not consume meat. Compared with medium-meat eaters, no-meat eaters were more likely to be single and users of dietary supplements. Women and high-educated individuals were less likely to be high-meat eaters, whereas overweight and obese individuals were more likely to be high-meat eaters. Total energy intake was similar between the four different meat consumption groups, but no-meat eaters had lowest total protein intake. Conclusions: This study identified important differences in sociodemographic, anthropometric, behavioural and dietary factors between menuCH participants with different meat-eating habits.